Property management service s’ effects on resident’s satisfaction with condominiumin Sungai Long - Chai, Ten Yee (2023)
This research was carried out to study the property management service s’ effect on resident s’ satisfaction with condominiums in Sungai Long. Four factors had been tested which are cleanliness, housing environment, safety and security as well as facilities and services. This study applied a quantitative research method. The target population of this research is residents who live in condominiums in Sungai Long, Primary data of this research was obtained through the distribution of 45 copies of questionnaires and was analyzed using the SPSS software.The constructs of the questionnaire were reliable as Cronbach's Alpha value of all the factors was above 0.7. The data analysis applied fort his research is the relative importance index, the four factors were ranked from most important to least important and the ranking is as follows cleanliness, housing environment, safety and security, facility and services.